Analysis Buying Motive in Indonesia Football Merchandise Store - Andipa Galuh Noersyeha; Adila Sosianika (Politeknik Negeri Bandung, 2018)
Football has become a popular sport all over the world, even its popularity far superior to other sports such as basketball and volleyball. Things like that used by everyone to earn income from this field of football, including selling football merchandise from start selling clothes, scarves, jersey, and other accessories. The sale of a football merchandise in Europe has been an influential source of income for the life of a club. This phenomenon is being started by some clubs in Indonesia to earn more revenue than selling merchandise. With a fairly large football support base in Indonesia, researchers want to analyze a person's purchasing motifs from hedonic motifs and utilitarian motives that affect a person's drive to buy and visit merchandise football stores in Indonesia. This study aims to determine whether these two motives can affect the impulse purchase and which motives tend to stronger influence the impulse purchase of someone. The research method used is descriptive statistical analysis, regression, and ANOVA using SPSS 22 to determine the effect of both motives to impulse buying.